OP0022 TNFI and TOFACITINIB monotherapy and comparative effectiveness in clinical practice: results from corrona registry. (15th June 2017) - Reed, GW; Gerber, RA; Shan, Y; Takiya, L; Dandreo, KJ; Gruben, D; Kremer, JM; Wallenstein, GV
Abstract : Background: TNF inhibitors (TNFi) can be used as monotherapy (mono) or in combination (combo) with conventional DMARDS (cDMARDS). Data from randomized clinical trials and European registries suggest there is evidence of better effectiveness of TNFi combo therapy than mono. Effectiveness of TNFi mono vs combo in US clinical practice, in particular among biologic naïve and experienced patients, has not been assessed. There have also been no assessments of tofacitinib (tofa) mono vs tofa combo nor tofa mono vs TNFi combo in US clinical practice. Tofacitinib is an oral Janus kinase inhibitor for the treatment of RA. Objectives: This study quantifies the prevalence and effectiveness of TNFi monotherapy use compared to TNFi combination therapy by line of therapy in US clinical practice. Secondary objectives were to compare tofa monotherapy use and effectiveness separately to tofa combo and to TNFi combo therapies. Methods: RA patients initiating a TNFi (adalimumab, etanercept, infliximab, golimumab, certolizumab pegol) or tofa with a six month follow-up in Corrona US were identified. A subcohort of TNFi initiations after 11/6/2012 (market approval of tofa) were used for comparisons with tofa initiators. We defined combo therapy as TNFi or tofa used with MTX only and mono as no use of any cDMARD. The primary outcome was achieving LDA (low disease activity) or remission based on CDAI (≤10) at 6 months. Patients switching to another biologic prior to 6 months were defined as non-responders. Secondary outcomes included modified ACR20/50/70 and mean change in CDAI. Combo and mono initiators were matched within line of therapy using a propensity score. Covariates for the model were selected if the standardized mean difference between the groups >0.1. Results: From 10/2001 to 8/2016 there were 7976 eligible TNFi initiations in Corrona, with 2511 (31%) mono initiations. Mono by line of therapy was 21%, 36% and 42% for 2nd, 3rd and 4th line therapy, respectively. There were 555 tofa initiations with 338 (61%) mono and mono rates of 47%, 58% and 63% for 2nd, 3rd and 4th line therapy, respectively. In the matched populations, across outcome measures (Table 1 ), TNFi combo was more effective than TNFi mono in 2nd line therapy (55.6% LDA vs 47.1% LDA) and differences diminished with 3rd line (43.2% vs 36.6%) and 4th line (32.0% vs 34.0%). Tofa combo therapy was similar to mono in the matched 3rd and 4th + line populations combined (35.2% LDA vs 31.1% LDA). Tofa mono was similar to TNFi combo therapy in the matched 3rd and 4th + line populations combined (33.6% LDA vs 37.5% LDA). Conclusions: TNFi monotherapy is common in U.S. clinical practice. TNFi monotherapy is less effective than combination therapy especially in biologic naïve patients or with one prior biologic. There is no evidence that tofacitinib monotherapy is less effective than tofa combination therapy or TNFi combination therapy in the outcome measures reported. Acknowledgements: This study is sponsored by Corrona, LLC. The Corrona RA registry has been supported through contracted subscriptions in the last two years by AbbVie, Amgen, Astra Zeneca, BMS, Crescendo, Eli Lilly and Company, Genentech, GSK, Horizon Pharma USA, Janssen, Momenta Pharmaceuticals, Novartis, Pfizer, Roche and UCB. Disclosure of Interest: G. Reed Shareholder of: Corrona, LLC, Employee of: Corrona, LLC, R. Gerber Shareholder of: Pfizer, Employee of: Pfizer, Y. Shan Employee of: Corrona, LLC, L. Takiya Shareholder of: Pfizer, Employee of: Pfizer, K. Dandreo Employee of: Corrona, LLC, D. Gruben Shareholder of: Pfizer, Employee of: Pfizer, J. Kremer Shareholder of: Corrona, LLC, Grant/research support from: AbbVie, Genentech, Lilly, Novartis, Pfizer, Consultant for: AbbVie, Amgen, BMS, Genentech, Lilly, Regeneron, Sanofi, Pfizer, Employee of: Corrona, LLC, G. Wallenstein Shareholder of: Pfizer, Employee of: Pfizer